Sistema de Facturación electrónica para el control de venta del local Tecnología Móvil A.C ubicado en el cantón Puebloviejo. - Escobar Villares, Reynaldo Boanerges (2022)
Mobile Technology A.C. is a commercial company from the city of Puebloviejo in the Province of Los Ríos, which is dedicated to the maintenance and sale of smartphones and electronic equipment. Currently, this place delivers physical invoices to its customers, therefore, the need arises to learn more about its way of managing, whose purpose is to minimize the errors that occur throughout the investigation. The objective of this study is to provide the reader with relevant information on the relevance of electronic invoicing, the benefits it provides and, in turn, the regulatory and tax framework to provide for its application, for which the exploratory and bibliographic method was applied, with the execution of an interview with the owner of the business.